Formulasi dan Evaluasi Kualitas Kordial Berbasis Jeruk Kalamansi pada Komoditas di Bukit Kor, Terengganu - Br Lubis, Tia Aulia; ardila, desi (Universitas Muhammadiyah Semarang, 2024)
Cordial is defined as a beverage product made from a mixture of water and sugar with a sugar solution of at least 65% or without other food ingredients or additives. Sugar solution of at least 65% or without other food ingredients or food additives permitted in accordance with applicable regulations. Kalamansi orange cordial is a processed product in the form of a sugar mixture made from kalamansi orange with a distinctive flavor. Kalamansi with a distinctive flavor. This study aims to evaluate the physical properties of kalamansi cordial drink with the addition of control treatment formulation, salt, pandan, and salt and pandan. The analysis carried out is color, viscosity, TSS, pH, sensory test. Results. This study shows that kalamansi cordial with the treatment of control, formulation A, formulation B, formulation C, and formulation D have the following colors ( 1,80; 2.60; 2.00; 2.37, viscosity (1.60; 2.60; 1.97; 2.70; CPs), TSS (73.70; 74.80; 73.70; 75.80 %), pH (3.52; 3.13; 3.35; 3.16). Physical properties of cordial base with control treatment had the best physical properties compared to the other 3 formulations. Taste sensory test and overall acceptance then the drink with formulation A has the best results because it has the highest physical properties.